Flexural reinforced concrete members with minimum reinforcement under low-velocity impact load - Warakorn Tantrapongsaton (2018)
© 2018 GEOMATE International Society. Under various accidental situations, reinforced concrete members may be subjected to low-velocity impact loading. To avoid the sudden failure due to high strain rate, an amount of reinforcement is required. This paper presents the finite element analysis of simple reinforced concrete beams under low-velocity impact load. Falling weights of 250 and 500 kg were dropped at 1.2 m high on the beam midspan. Shear-to-bending capacity ratios varied from 0.9 to 11.3. Sixteen beams under different beam reinforcement ratios and with minimum static reinforcements were studied. The magnitude of the impact force, reactions, crack pattern, strains in beam reinforcements were examined. Shear crack, plastic strain in stirrups and shear plug damage were observed on the high flexural resistance specimens while the specimens with low flexural resistance completely failed in flexural failure. Finally, it could be concluded that the impact loading design requires more amount of reinforcement, especially transverse reinforcement to avoid the brittle shear failure. In addition, the longitudinal reinforcement should be increased to 2-4 times from the design in static load case to prevent sudden flexural failure of the structures.